HOW SOCIAL NETWORKS IMPACT PEOPLE’S DAILY LIVES - Turmamatova, Shakhnoza; Akhmedov, Utkir (International Conference on Science, Education & Law, 2025)
This article analyzes  the influence of social networks on people’s everyday lives. It discusses both the advantages and disadvantages of using social media, focusing on its impact on communication, relationships, and lifestyle habits. The paper emphasizes that social platforms enable users to connect globally  share information and express themselves freely. Nevertheless, it also points out negative affects  such as addiction, loss of privacy, and reduced face-to-face communication. The study concludes that social media has become an integral part of modern life, influencing people’s behavior, thinking, and social interactions in various ways.